18F-fluorodeoxyglucose positron emission tomography/computed tomography in diagnosis of post-transplant lymphoproliferative disorder. Issue 3 (March 2014) - Panagiotidis, Emmanouil; Quigley, Ann-Marie; Pencharz, Deborah; Ardeshna, Kirit; Syed, Rizwan; Sajjan, Rakesh; Bomanji, Jamshed
Abstract The aim of the present study was to investigate the role of 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) in the diagnosis of post-transplant lymphoproliferative disorder (PTLD), a serious complication of solid organ and bone marrow transplant. Between January 2004 and January 2012, 40 patients (22 males; median age 52 ± 17.4 years, range 11–77 years) underwent 18F-FDG PET/CT scans in our department for diagnostic evaluation of PTLD. Twenty-three (57.5%) patients had negative 18F-FDG PET/CT and 17 (42.5%) had a positive examination. In five patients PET/CT revealed extranodal disease (adrenal, pleural, spleen, liver, lung, esophagus and bone involvement). On the basis of our results, 18F-FDG PET/CT had a sensitivity of 88.2% (95% confidence interval [CI] 0.62–0.98), a specificity of 91.3% (CI 0.70–0.98), a positive predictive value of 88.2% (CI 0.62–0.98) and a negative predictive value of 91.3% (CI 0.70–0.98). The diagnostic performance of CT in patient-based analysis was: a sensitivity of 87.5% (CI 0.60–0.97), a specificity of 88.8% (CI 0.64-0.98), a positive predictive value of 87.5% (CI 0.60–0.97) and a negative predictive value of 88.8% (CI 0.64–0.98). PET/CT in five cases revealed more findings than CT, upstaging the disease, and revealed three extranodal findings, not visualized in conventional imaging. 18F-FDG PET/CT plays a significant role in the setting of PTLD diagnosis, demonstrating its high accuracy in detecting PTLD.